PKM: Membangun Kelincahan Rantai Pasok melalui Penguatan Kepemimpinan Strategis di Era VUCA - Ezar Amrullah; Yudistira Krisna Pratama (Al-DYAS, 2026)
Although the urgency of strategic leadership in building supply chain agility in the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era has been widely recognized, practice in the field still reveals weak strategic governance and delayed adoption of digital technologies among partners, creating a significant gap between industrial agility demands and managerial practices that remain focused solely on efficiency. This Pengabdian Kepada Masyarakat (PKM) community engagement program aimed to strengthen partners’ understanding and awareness of strategic leadership mediated by dynamic capabilities and digital transformation in fostering supply chain agility. The approach employed participatory dissemination involving the community of formal workers in Kawasan Industri Kendal (KIK), small and medium industries (IKM), university students, and the general public, with evaluation focusing on participants’ cognitive understanding and satisfaction levels. The results of the PKM indicated a significant increase in partners’ understanding of strategic leadership, dynamic capabilities, digital transformation, and supply chain agility, accompanied by a high level of participant satisfaction with both the content and the program design. These findings affirm that strategic leadership cannot stand alone without the support of digital technologies, as digital technologies play a role in breaking through information silos, accelerating information flows, and reducing ripple effects in the supply chain, thereby requiring cross-functional integration and real-time information systems to minimize the reinforcement of information silos. The strength of this PKM lies in the implementation of a systematic program design that generated tangible impact in raising partners’ awareness, whereas its main limitations include low participation from entrepreneurial groups and the still-limited technical capacity of online platforms. The recommendations proposed include expanding outreach activities, providing more flexible participation channels, and strengthening the sustainability of PKM through digital community-based mentoring so that the transformation toward strategic leadership and agile supply chains can be accelerated in a sustainable manner.